2022-RA-262-ESGO Predictors of oncologic outcome in recurrent cervical cancer patients receiving phase 1 cancer therapy. (20th October 2022) - Son, Ji; Lin, Heather Y; Fu, Siqing; Dumbrava, Ecaterina E; Karp, Daniel D; Naing, Aung; Pant, Shubham; Piha-Paul, Sarina A; Rodon, Jordi; Subbiah, Vivek; Tsimberidou, Apostolia M; Yap, Timothy A; et al.
Abstract : Introduction/Background: Few treatment options exist in recurrent cervical cancer, which makes phase 1 clinical trials a compelling option. In order to identify candidates for referral, we analyzed factors predictive of response and survival in cervical cancer patients referred to phase 1 trials. Methodology: Cervical cancer patients who received at least 1 cycle of a phase 1 agent between 2014–2022 were retrospectively reviewed. Clinical and pathologic data were abstracted, Log-rank test was used to test the difference in progression-free survival (PFS) and overall survival (OS). Multivariable regression analysis was performed for predictors of response and survival. Results: 65 patients met eligibility. At trial entry, patient characteristics included the following median (range) values: age 41 years (20, 74), 3 prior therapies (1, 7), and 5-month progression-free interval before trial (1, 32). 67.7% had squamous carcinoma, 27.7% adenocarcinoma, 4.5% other. The rate of distant metastasis was 84.6%. The most common alterations included PIK3CA (46.5%), PDL1+ (46.2%), EPH (30.0%), and CREBBP (23.1%). 23.1% received a prior check point inhibitor. The phase 1 trials were immunotherapy (58.5%) and targeted therapy (41.5%). In all, objective response rate was 10.8%, median PFS 3.6 months, and OS 9.3 months. On multivariable analysis of significant covariates, factors at study entry that were associated with worse survival were the presence of bone metastasis (PFS 1.6 vs 4.4 months, HR 2.8; OS 3.8 vs 10.0 months, HR 3.9; both p<0.001), and absolute lymphocyte count (ALC) <1k/μl (PFS 1.8 vs 5.2 months, HR 2.9; OS 7.0 vs 10.6 months, HR 3.2; both p<0.0009). Other factors associated only with negative OS were Hb<11g/dl, absolute neutrophil count>4.7k/μl, and current or former smoking status. The rate of grade 3+ treatment-related adverse events was 16.9%. Conclusion: The presence of bone metastasis and ALC below normal range at phase 1 study entry portend poor survival in recurrent cervical cancer patients.